COPD with Eosinophilic Inflammation is Susceptible to Particulate Air Pollution Exposure - Amja Manullang; Chi-Li Chung; Yueh-Lun Lee; Tzu-Hsuen Yuan; Huan Minh Tran; Firdian Makrufardi; Kian Fan Chung; Kang-Yun Lee; Jer-Hwa Chang; Hsiao-Chi Chuang (Aerosol and Air Quality Research)
Abstract Chronic obstructive pulmonary disease (COPD) has been linked to air pollution exposure. Air pollution has been associated with eosinophilic inflammation of respiratory disease. The objective of this study was to determine associations between air pollution and eosinophilic inflammation in COPD. A cross-sectional study was conducted on 291 COPD patients recruited from hospitals in Taipei between January 2014 and 2021, including 147 patients with eosinophil blood count ≥ 2% and 144 patients < 2%. Land use regression (LUR) model was used to estimate exposure levels to particulate matter with an aerodynamic diameter of < 10 µm (PM10), PM2.5 (< 10 µm), nitrogen oxides (NOx) and nitrogen dioxides (NO2). We investigated associations of air pollution with COPD outcomes by performing a linear regression approach. A two-pollutant approach was applied to examine the associations of PM10 or PM2.5 with NOx or NO2 in COPD with eosinophilic inflammation. An increase of 1 µg m−3 in PM10 was associated with a 0.62% (95% CI: −1.10%, −0.13%) decrease in the forced vital capacity (FVC) in COPD. An increase of 1 µg m−3 in PM2.5 was associated with a 0.38% (95% CI: −0.71%, −0.05%) decrease in the FVC. A 1 µg m−3 increase in PM10 was associated with a 0.92% (95% CI: −1.68%, −0.16%) decrease in the FVC in COPD patients with eosinophilic inflammation. A 1 µg m−3 increase in PM2.5 was associated with an increase of 0.26 points (95% CI: −1.68%, −0.16%) in the COPD Assessment Test (CAT) and a 0.03-times year−1 (95% CI: 0.01, 0.05) increase in the acute exacerbation (AE) of COPD eosinophilic inflammation. Associations of PM10 and PM2.5 with lung function decline in COPD eosinophilic inflammation were confirmed by the two-pollutant model. Exposure to particulate air pollution increased the risk of deleterious health outcomes in COPD with eosinophilic inflammation. COPD with eosinophilic inflammation may represent a susceptible group to particulate air pollution exposure.